2006
DOI: 10.1007/s00264-006-0164-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolated varus intertrochanteric osteotomy for hip dysplasia in 52 patients: long-term results

Abstract: Great strides have been made in the field of total hip arthroplasty, but the issue of wear and osteolysis continue to be a problem, mostly for young adults. For this population varus rotational osteotomy still remains a viable alternative to total hip arthroplasty. The purpose of this prospective study was to describe the indications, the technique and the functional outcome of an isolated varus femoral osteotomy in 52 patients with hip dysplasia. We obtained very good results with a significant improvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…According to reports that have described the results of intertrochanteric varus osteotomy of the femur for developmental dysplasia of the hip, the indications for this procedure include patients having mild acetabular dysplasia [10,11,31]. One author reported observing no significant differences in survival rate between patients treated with periacetabular osteotomy and those treated with intertrochanteric varus osteotomy, if patients with more than five degrees of CE angle were selected preoperatively [31].…”
Section: Discussionmentioning
confidence: 99%
“…According to reports that have described the results of intertrochanteric varus osteotomy of the femur for developmental dysplasia of the hip, the indications for this procedure include patients having mild acetabular dysplasia [10,11,31]. One author reported observing no significant differences in survival rate between patients treated with periacetabular osteotomy and those treated with intertrochanteric varus osteotomy, if patients with more than five degrees of CE angle were selected preoperatively [31].…”
Section: Discussionmentioning
confidence: 99%
“…Ansaria et al [62] reported a retrospective study that supported the use of isolated varus proximal femoral osteotomy as a treatment option for young adults with DDH and particularly in patients with ipsilateral longer leg, even when early degenerative change was present. Koulouvaris et al [63] reported the long-term results in 52 patients who underwent the varus ITO were very encouraging, which showed survival probability was 93 % at nine years. However, Ito et al [64] reported the results of 55 varus ITOs in 46 patients with hip dysplasia after the mean 17 years of follow-up.…”
Section: Varus Intertrochanteric Osteotomymentioning
confidence: 95%
“…The rationale for the use of realigning varus and/or valgus osteotomies is to reduce stress throughout the cartilage surfaces in a hip that is compromised mechanically 59 . Ito et al 60 stated that intertrochanteric osteotomy is worthwhile in hips with Tönnis grade-0, 1, or 2 osteoarthritis with a spherical femoral head and mild dysplasia (Table II).…”
Section: Femoral Osteotomymentioning
confidence: 99%